Advances in Conceptual Modeling ER 2015 Workshops AHA, CMS, EMoV, MoBID, MORE-BI, MReBA, QMMQ, and SCME, Stockholm, Sweden, October 19-22, 2015, Proceedings - Jeusfeld, Manfred A.; Karlapalem, Kamalakar (Information Systems and Applications, incl. Internet/Web, and HCI, 2015)
This book constitutes the refereed proceedings of seven workshops and a symposium, held at the 34th International Conference on Conceptual Modeling, ER 2015, in Stockholm, Sweden. The 26 revised full and 8 invited papers were carefully reviewed and selected out of 52 submissions to the following events: Conceptual Modelling for Ambient Assistance and Healthy Ageing, AHA-2015; Conceptual Modelling of Services, CMS-2015; Event Modelling and Processing in Business Process Management, EMoV-2015; Modelling and Management of Big Data, MoBID-2015; Modelling and Reasoning for Business Intelligence, MORE-BI-2015; Conceptual Modelling in Requirements Engineering and Business Analysis, MREBA-2015; Quality of Modelling and Modelling of Quality, QMMQ-2015; and the Symposium on Conceptual Modelling Education, SCME-2015.